Foreign policy decision-making - Snyder, Richard C ( ed.) (New York, 1962)
Eight years have passed since the original publication of De cision-Making as an Approach to the Study of International Poli tics. Much has happened to the relevant literature since 1954, including advances in decision theory, in organizational theory, and in foreign policy analysis generally. Doubtless these develop ments would have heavily influenced a major revision of the scheme; and certainly if we were starting from scratch, present analytical foundations would permit a much improved presenta tion. Continued demand for the monograph has prompted The Free Press to reprint it together with (1) an empirical application (Snyder and Paige, 1958); (2) one of the most penetrating criti cisms of the approach (McClosky, 1956); and (3) an attempt to link decision-making to other types of analyses of international relations (Brody, 1960). Not all of the subsequent conceptualiza tion and research that is directly or indirectly an outgrowth of the earlier formulation has yet been published (for example, Snyder and Paige, The United States Decision to Resist Aggres sion in Korea, 1950, is to be published by Ronald Press Com pany; and Dean Pruitt, "Problem Solving in the Department of State," Program of Graduate Training and Research in Inter national Relations, Northwestern University, March, 1961). Many suggested refinements and extensions, however, can be found in Snyder and Robinson, National and International De cision-Making (1961).
Keywords: International Relations